Pendeteksian Cedera Jatuh Pada Kursi Roda Berbasis Mikrokontroler - Fezya Noviratama; Mohammad Hafiz Hersyah (CHIPSET, 2022)
In this study, the detection of falls in wheelchair users aims to make it easier for families to provide assistance when an injury occurs in a wheelchair so that the consequences can be minimized. In this study, the GY-521 sensor was used to detect the tilt of the wheelchair and a pulse sensor to detect the user's pulse. The output of the system in this study is a buzzer and sms notification. If the detected angle is > 25° (pitch angle) and > 30° (roll angle) then it is detected as a fall injury to the wheelchair. And if a small heart rate equals 60 and a large heart rate equals 100 it will be detected as an abnormal heartbeat. In this study, tests for fall detection were carried out on users who have different weights and for heart rate conditions, tests were also carried out when the wheelchair was used or not in use. So it can be concluded that the tilt angle of the wheelchair fall detection system is influenced by the weight of the wheelchair user.